A Rancangan Aplikasi Marketplace Umkm Aerilove Accecories Di Kota Padang Menggunakan Aplikasi Blogger - Kurniawan, Bayu Kurniawan; Salsabila, Alfieza Salsabila; Hardati, Siti Zaharatal Hardati (CV. ITTC INDONESIA, 2023)
Abstract: This article discusses the importance of utilizing internet technology, especially the Blogspot platform, in promoting Micro, Small and Medium Enterprises (MSMEs). In the midst of technological developments and digital trends, MSMEs need to understand how to use Blogspot as an effective promotional tool. This research focuses on the MSME Aerilove Accessories which operates in the fashion accessories sector. The research results show that using Blogspot provides benefits such as expanding market reach, increasing brand visibility, and interaction with customers. MSMEs need guidance and support to optimize the use of Blogspot. It is hoped that this research can provide practical guidance to MSMEs in utilizing Blogspot as an effective promotional tool in the digital era, as well as contributing to sustainable local economic growth. Keywords : Micro, Small and Medium Enterprises (MSMEs), Digital Marketing, Blogger.. Abstrak: Pemanfaatan teknologi internet, khususnya platform Blogspot, dalam mempromosikan Usaha Mikro, Kecil, dan Menengah (UMKM). Di tengah perkembangan teknologi dan tren digital, UMKM perlu memahami cara memanfaatkan Blogspot sebagai alat promosi yang efektif. Penelitian ini fokus pada UMKM Aerilove Accessories yang bergerak di bidang aksesori fashion. Hasil penelitian menunjukkan bahwa penggunaan Blogspot memberikan manfaat seperti perluasan jangkauan pasar, peningkatan visibilitas merek, dan interaksi dengan pelanggan. UMKM perlu mendapatkan bimbingan dan dukungan untuk mengoptimalkan penggunaan Blogspot. Penelitian ini diharapkan dapat memberikan panduan praktis kepada UMKM dalam memanfaatkan Blogspot sebagai alat promosi yang efektif dalam era digital, serta berkontribusi pada pertumbuhan ekonomi lokal yang berkelanjutan. Kata Kunci : Usaha Mikro Kecil Menengah (UMKM), Pemasaran Digital, Blogger.